A Multicenter Preliminary Study of Cangrelor following Thrombectomy Failure for Refractory Proximal Intracranial Occlusions - Marnat, G.; Delvoye, F.; Finitsis, S.; Lapergue, B.; Gariel, F.; Consoli, A.; Desilles, J.-P.; Mazighi, M.; Dargazanli, C.; Bourcier, R.; Darcourt, J.; Chalumeau, V.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Rescue endovascular and pharmacologic approaches are increasingly being adopted after recanalization failure of acute large-vessel occlusion strokes with mechanical thrombectomy, with encouraging results. The safety and efficacy of glycoprotein IIb/IIIa inhibitors in ischemic stroke have been investigated, though cangrelor, a recent intravenous P2Y12-receptor inhibitor with a rapid onset/offset of action and a short half-life, may be a valuable option. We compared the safety and efficacy of cangrelor with those of glycoprotein IIb/IIIa inhibitors for refractory occlusions.MATERIALS AND METHODS: We performed a retrospective analysis of the ongoing prospective, multicenter, observational Endovascular Treatment in Ischemic Stroke Registry in France between May 2012 and February 2020. Refractory intracranial occlusions of the anterior and posterior circulation were included and defined as recanalization failure of large-vessel occlusion stroke, perioperative target artery reocclusion, or high risk of early reocclusion related to an arterial wall lesion. The primary end point was a favorable outcome, defined as a 90-day mRS of 0–2. Secondary end points were reperfusion, intracranial hemorrhage, and procedural complications.RESULTS: Among 69 patients, 15 were treated with cangrelor, and 54, with glycoprotein IIb/IIIa inhibitors. The favorable outcome (adjusted OR = 2.22; 95% CI, 0.42–11.75; P = .348) and mortality (adjusted OR = 0.44; 95% CI, 0.06–3.16; P = .411) rates were similar in both groups. There was no difference in the rates of any intracranial hemorrhage (adjusted OR = 0.40; 95% CI, 0.08–2.09; P = .280), symptomatic intracranial hemorrhage (6.7% versus 0.0%, P = .058), or procedural complications (6.7% versus 20.4%, P = .215). Reperfusion rates were higher in the cangrelor group, though the difference did not reach statistical significance (93.3% versus 75.0% for modified TICI 2b–3; adjusted OR =10.88; 95% CI, 0.96–123.84; P = .054).CONCLUSIONS: Cangrelor seems to be as safe as glycoprotein IIb/IIIa inhibitors for managing refractory intracranial occlusion and leads to satisfactory brain reperfusion. Cangrelor is a promising agent in this setting, and additional studies are warranted to confirm our findings.ASAacetylsalicylic acidGPIIb/IIIaglycoprotein IIb/IIIaICHintracranial hemorrhagemTICImodified TICIsICHsymptomatic intracranial hemorrhage